2018
DOI: 10.1186/s13068-018-1287-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and metabolomic analysis of the cellular biomarkers related to inhibitors tolerance in Zymomonas mobilis ZM4

Abstract: BackgroundToxic compounds present in both the hydrolysate and pyrolysate of lignocellulosic biomass severely hinder the further conversion of lignocellulose-derived fermentable sugars into useful chemicals by common biocatalysts like Zymomonas mobilis, which has remarkable advantages over yeast. Although the extra detoxification treatment prior to fermentation process can help biocatalysts to eliminate the inhibitory environment, it is not environment friendly and cost effective for industrial application. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 91 publications
5
15
0
Order By: Relevance
“…The transcriptomics results demonstrated that genes encoding ABC transporters such as ZMO_RS08315, ZMO_RS04690, ZMO_RS01550, ZMO_RS02545 and ZMO_RS01130 were signi cantly up-regulated in ZM532 (Additional le 7, 8: Table S7, S8). The up-regulation of ABC transporter genes were consistent with results from acidic-pH treatment [41,42]. The up-regulation of ABC transporters may enhance and sustain the cytoplasmic pH homeostasis in mutant strain ZM532 under AF conditions.…”
Section: Genome Gene and Protein Correlationssupporting
confidence: 78%
See 2 more Smart Citations
“…The transcriptomics results demonstrated that genes encoding ABC transporters such as ZMO_RS08315, ZMO_RS04690, ZMO_RS01550, ZMO_RS02545 and ZMO_RS01130 were signi cantly up-regulated in ZM532 (Additional le 7, 8: Table S7, S8). The up-regulation of ABC transporter genes were consistent with results from acidic-pH treatment [41,42]. The up-regulation of ABC transporters may enhance and sustain the cytoplasmic pH homeostasis in mutant strain ZM532 under AF conditions.…”
Section: Genome Gene and Protein Correlationssupporting
confidence: 78%
“…The transcriptome pro le indicates ZMO_RS04970, ZMO_RS03175, ZMO_RS04970 were up-regulated in both strains and are involved in respiratory chain for energy production while ZMO_RS06760, ZMO_RS07025 and ZMO_RS02530 were down-regulated (Additional le 7, 8: Table S7, S8). Previous studies have con rmed that these proteins are essential of higher ethanol production and growth [42] however, up-and down-regulation of genes involved in various biological processes in response to various stressors.…”
Section: Candidate Genes and Proteins Involved In Energy Generation And Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Ndh activity was shown to confer advantage for Z. mobilis aerobic growth and flocculation on minimal media (Jones-Burrage et al, 2019). Upregulation of ndh and some other oxidoreductase genes were observed under lignocellulose inhibitor stress (Chang et al, 2018). Hayashi et al (2015) demonstrated positive impact of Ndh activity on Z. mobilis salt stress resistance.…”
Section: Zymomonas Mobilis: An Example Of Uncoupled Energy Metabolismmentioning
confidence: 99%
“…Z. mobilis has many desirable industrial characteristics, such as high-specific ethanol productivity, high ethanol yield, high ethanol tolerance and a wide fermentation pH range [ 2 , 3 , [6] , [7] , [8] ]. Metabolic engineering can provide new characteristics and capabilities to Z. mobilis like expand its substrate range, remove competing pathways and enhance its tolerance to ethanol and to other lignocellulosic hydrolysate inhibitors as aliphatic acids, furan aldehydes and furfural [ [9] , [10] , [11] ]. However, considering the variety of factors involved in the response to high concentrations of these compounds makes it difficult to devise new metabolic engineering strategies to generate tolerant strains, and for this reason still important to find novel genes and traits related to ethanol tolerance and to other biomass-derived growth inhibitors [ [8] , [9] , [10] , [11] , [12] ]…”
Section: Introductionmentioning
confidence: 99%